The impact of Ethno-Realistic Mathematics Education-based e-module in strengthening students’ problem-solving abilities - Alghiffari, Eka Kevin; Prahmana, Rully Charitas Indra; Evans, Brian (Universitas Hamzanwadi, 2024)
Mathematics education in Indonesia faces challenges primarily due to the limited problem-solving skills of students, prompting a need for effective teaching materials to enhance classroom learning. Despite this, many educators still rely on conventional methods that are less effective in fostering mathematical understanding. Consequently, there is a demand for alternative resources that can better support mathematics education. This study aims to develop a valid and practical e-module based on Ethno-Realistic Mathematics Education (Ethno-RME) to improve problem-solving abilities among eighth-grade students. Employing a design research approach within the development studies framework, the study includes preliminary and formative evaluation stages. Evaluation tools encompass expert assessments of content and media quality, walkthroughs, documentation, and problem-solving assessments. The outcome is an Ethno-RME-based e-module focused on number patterns, validated through expert reviews and positively evaluated for practicality by students. This research highlights the e-module's potential to significantly enhance students' mathematical problem-solving skills, offering educators an innovative tool to support effective mathematics teaching.